2012
DOI: 10.1007/s11605-011-1727-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism Underlying the Detection of Colorectal Cancer by 18F-2-Fluoro-2-Deoxy-d-Glucose Positron Emission Tomography

Abstract: Our molecular-based analysis suggested that FDG accumulation due to induction of glucose uptake proteins might be associated with the hypoxic environment in tumors rather than the tumor growth. Therefore, for assessing the efficacy of chemotherapy using FDG-PET, we must keep in mind that SUV does not indicate the tumor growth directly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 26 publications
2
18
0
1
Order By: Relevance
“…The increased energy provided by GLUT1 overexpression likely plays a role in both HCC and Meta tumor growth; therefore, the reason for the contrasting PCNA results is unclear. However, the PCNA expression in Meta specimens was consistent with a previous study (20). These results indicate that SUV cannot always estimate tumor growth or prognosis in the patients with liver metastasis of colorectal cancer.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The increased energy provided by GLUT1 overexpression likely plays a role in both HCC and Meta tumor growth; therefore, the reason for the contrasting PCNA results is unclear. However, the PCNA expression in Meta specimens was consistent with a previous study (20). These results indicate that SUV cannot always estimate tumor growth or prognosis in the patients with liver metastasis of colorectal cancer.…”
Section: Discussionsupporting
confidence: 90%
“…Reverse transcription was carried out with 1 µg RNA, and the resulting cDNA was analyzed by real-time PCR with Power SYBR Green PCR Master Mix and the ABI Prism 7000 (Applied Biosystems, Foster, CA, USA). Target-specific oligonucleotide primers and probes were previously described (19,20). As endogenous control, the amplification of 18S rRNA was used.…”
Section: Methodsmentioning
confidence: 99%
“…The expression of HIF-1α and the correlated target genes, including Glut-1, is regulated by the PI3K/protein kinase B (Akt) pathway (23,24). However, it remains unclear whether the PI3K/Akt signal pathway is involved in the regulation of FDG uptake (15,16,25,26). Consequently, the association between FDG and hypoxia markers must be studied further.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, KRAS mutants with low SUV, high MPP, and high BF demonstrated increased mcm2 expression, implying a proliferative phenotype. Unlike some tumors, previous data indicate that 18 F-FDG uptake in primary CRC is unrelated to proliferation (32) whereas a recent study has shown that induction of proliferation in CRC tissue samples did not increase 18 F-FDG uptake (although induction of HIF-1 did increase SUV) (33). Thus, there is concordance between the histologic and imaging findings for both of these subgroups of KRAS mutants.…”
Section: Discussionmentioning
confidence: 77%